KENDALA DAN TANTANGAN TIM PENGAWASAN ORANG ASING (TIMPORA) DALAM PENGAWASAN DAN PENDATAAN WNA DI KOTA TANGERANG: Obstacles and Challenges for the Foreigners Surveillance Team (TIMPORA) in Monitoring and Recording Foreign Nationals in the City of Tangerang - Ericha Kania Ighfirly; Tri Sulistyowati (Faculty of Law, Universitas Trisakti, 2026)
he monitoring and data collection of foreign nationals in Tangerang City is carried out by the Foreigners Monitoring Team (TIMPORA) as an inter-agency coordination forum. The high level of industrial and service activity in Tangerang City has led to increased mobility of foreign nationals, requiring effective and integrated monitoring. The research question is: What are the obstacles and challenges faced by TIMPORA in supervising and collecting data on foreign nationals in Tangerang City? This research uses a qualitative, descriptive method, using secondary data, which is analysed qualitatively, and conclusions are drawn deductively. The results of the discussion and conclusions show that TIMPORA has a strategic position in the regional immigration monitoring system, but its implementation has not been optimal due to weak inter-agency coordination, limited resources, and the lack of integration of the foreign national data collection system. In addition, the high mobility of foreign nationals and low community participation also pose challenges to supervision. Therefore, strengthening the role of TIMPORA requires increased institutional synergy, integration of cross-sector data collection systems, increased capacity of officials, and active involvement of local government and the community to realise effective and accountable supervision of foreign nationals in Tangerang City.